How Economists Help Central Government Think: Survey Evidence from the UK Government Economic Service. Issue 13 (3rd October 2019) - Anand, Paul; Roope, Laurence; Ross, Andy
ABSTRACT: Economic thinking is widely used now across most areas of government activity, though there is not much research on what professional economists do. This paper, therefore, develops and reports on a survey of over 500 members of the UK Government Economic Service, which we use to shed light on the activities and thinking of practitioners. We find, inter alia, that professional economics can be seen as drawing on at least four distinct economic paradigms, that the uses of economics vary significantly between areas of government and that whilst significant use of research can be made, this is not necessarily a defining aspect of professional practice.